2013
DOI: 10.1371/journal.pone.0082115
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Using a Self-Lavaging Device for Cytology and HPV Testing for Cervical Cancer Screening: Findings from a Pilot Study

Abstract: Self-sampling could increase cervical cancer screening uptake. While methods have been identified for human papillomavirus (HPV) testing, to date, self-sampling has not provided adequate specimens for cytology. We piloted the validity and reliability of using a self-lavaging device for cervical cytology and HPV testing. We enrolled 198 women in New York City in 2008–2009 from three ambulatory clinics where they received cervical cancer screening. All were asked to use the Delphi Screener™ to self-lavage 1–3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…[4][5][6][7] Mycoplasma and Ureaplasma spp are among the organisms most frequently isolated from both placenta and amniotic fluid (AF) in spontaneous preterm delivery. [8][9][10] The standard microbial culture method for detecting microorganisms, such as Mycoplasma, Ureaplasma, and other aerobic or anaerobic bacteria, requires 1 week to obtain the results.…”
mentioning
confidence: 99%
“…[4][5][6][7] Mycoplasma and Ureaplasma spp are among the organisms most frequently isolated from both placenta and amniotic fluid (AF) in spontaneous preterm delivery. [8][9][10] The standard microbial culture method for detecting microorganisms, such as Mycoplasma, Ureaplasma, and other aerobic or anaerobic bacteria, requires 1 week to obtain the results.…”
mentioning
confidence: 99%
“…When reported, relative sensitivities for CIN2 + were low and ranged between 33% and 75%. 159 , 160 Several studies have shown comparable or improved specificity of self-collected cytology compared to clinician-collected samples. 155 , 157 , 159 …”
Section: Self-sampling Beyond Hpv Testingmentioning
confidence: 99%
“…When reported, relative sensitivities for CIN2 + were low and ranged between 33% and 75%. 159,160 Several studies have shown comparable or improved specificity of self-collected cytology compared to clinician-collected samples. 155,157,159 In a recent prospective cohort study, Loopik et al showed reflex cytology is feasible on hrHPV-positive self-samples and could be considered as an additional triage test for immediate referral to decrease loss to follow-up in screening.…”
Section: Self-sampling Beyond Hpv Testing Cytologymentioning
confidence: 99%
See 1 more Smart Citation
“…No campo de pesquisa da biologia dos tumores, a cultura de células tem sido o pilar para o avanço dessa área. Em parte, isso se deve à identificação de que muitas linhagens apresentam aberrações genéticas e epigenéticas que também são encontradas em biópsias do tecido tumoral correspondente (SAAF et al, 2007;VAN STAVEREN et al, 2009;MACLEOD et al, 1999;JONES et al, 2013;GAYET et al, 2001). Nesse contexto, no estudo realizado por Mouradov e colaboradores (2014)…”
Section: Linhagens De Câncer Colorretal: Ht29 E Hct116unclassified